2015
DOI: 10.1371/journal.pone.0132905
|View full text |Cite
|
Sign up to set email alerts
|

Access to Education for Orphans and Vulnerable Children in Uganda: A Multi-District, Cross-Sectional Study Using Lot Quality Assurance Sampling from 2011 to 2013

Abstract: ObjectivesThis study estimates the proportion of Orphans and Vulnerable Children (OVC) attending school in 89 districts of Uganda from 2011 – 2013 and investigates the factors influencing OVC access to education among this population.MethodsThis study used secondary survey data from OVCs aged 5 – 17 years, collected using Lot Quality Assurance Sampling in 87 Ugandan districts over a 3-year period (2011 – 2013). Estimates of OVC school attendance were determined for the yearly time periods. Logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…The study suggests strengthening families' and guardian's economic capacity through income generating activities, social and emotional inclusive support programs, inter-organizational coordination and launching institutional care/ promoting local adoption for the abandoned and orphans. In the similar way, the study in Uganda by Olanrewaju et al [32] revealed that despite the implementation of free universal primary education, there is high prevalence of children living in vulnerable environment with high prevalence of HIV/AIDS, prolonged conflict (particularly, in the northern region) and extreme poverty. Based on SDGs, accessing basic education has been identified as one of the crucial factors to ensure child social protection [33].…”
Section: Prevalence Of Children Living In Vulnerable Environmentmentioning
confidence: 82%
“…The study suggests strengthening families' and guardian's economic capacity through income generating activities, social and emotional inclusive support programs, inter-organizational coordination and launching institutional care/ promoting local adoption for the abandoned and orphans. In the similar way, the study in Uganda by Olanrewaju et al [32] revealed that despite the implementation of free universal primary education, there is high prevalence of children living in vulnerable environment with high prevalence of HIV/AIDS, prolonged conflict (particularly, in the northern region) and extreme poverty. Based on SDGs, accessing basic education has been identified as one of the crucial factors to ensure child social protection [33].…”
Section: Prevalence Of Children Living In Vulnerable Environmentmentioning
confidence: 82%
“…A cross sectional baseline survey of OVCs and their caregivers in 5 LGAs in Lagos State, Nigeria was carried out in February 2015. The LGAs were purposefully selected based on USAID guidelines (the agency providing the funding for this OVC intervention project) dictated by the burden of HIV and non-presence of other implementing partners in the LGAs.…”
Section: Methodsmentioning
confidence: 99%
“…The advent of HIV epidemics in the early 1990s and the attendant mortality before availability of antiretroviral drugs left many households without breadwinners1. As a result, many households suffer material deprivation which is one of the consequences of AIDS mortality 5 . The immediate effect of household deprivation often manifest in non-availability of food which leads to hunger.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in other studies, Ainsworth and Filmer (2006), Campbell et al (2010) and Olanrewaju et al (2015) who conducted studies on orphans and vulnerable and their access to other support services such as education and psychosocial support, it was found that socio-demographic and household factors also influenced receipt of these support services as it was specifically stated that wealth, gender and regional variation are all more important predictors of receipt of support services. Therefore, this study supports other studies including those of Foster and Germann (2002), Harber (2009) and Datta (2013) that proposed community-based care as viable approach to taking care of orphans and vulnerable children as it places children at the centre of all development programmes, ensures different levels of community ownership and participation (Ansell and Young, 2004;Sanou et al, 2009) and believed to be the most cost-effective strategy for providing care and support to OVC but proposes that interventions on service provision for OVC should be integrated into other programs such as the Hard-to-Reach (HTR) programs and the new Community Health Influencers, Promoters and Services (CHIPS) program Community Health Influencers, Promoters and Services (CHIPS) program (Adebayo, 2017) as this would help improve service provision to households, case management, tracking, monitoring and follow-up of services and militate against the influence of socio-demographic factors such as Victor 169 region of residence.…”
Section: Household Characteristicsmentioning
confidence: 95%